Penggabungan Perkara Tindak Pidana Perusakan Lingkungan Hidup dan Tindak Pidana Korupsi dalam Pemeriksaan di Pengadilan Tindak Pidana Korupsi - July Esther; Martono Anggusti; Roida Nababan; Alex Denischael Berutu (Jurnal Hukum Lex Generalis, 2025)
This study examines the possibility of joining environmental destruction crimes and corruption offenses before the Corruption Crimes Court. It employs normative legal research with statutory and conceptual approaches. The findings indicate that the limited jurisdiction of the Corruption Court under Article 6 of Law No. 46 of 2009 obstructs the implementation of fast, simple, and low-cost justice, as environmental cases must be tried separately. In fact, the concurrence doctrine under the Criminal Code allows case consolidation. Therefore, this study recommends expanding the Court’s jurisdiction and establishing integrated prosecution guidelines to enhance legal effectiveness.